Spinosad resistance in field populations of melon fly, Zeugodacus cucurbitae (Coquillett), in Hawaii. Issue 12 (13th August 2021) - Hsu, Ju‐Chun; Chou, Ming‐Yi; Mau, Ronald FL; Maeda, Colby; Shikano, Ikkei; Manoukis, Nicholas C; Vargas, Roger I
Abstract: BACKGROUND: Control of Zeugodacus cucurbitae, a serious agricultural pest worldwide, often includes or is dependent on the use of spinosad‐based insecticides. This is especially the case in Hawaii, where GF‐120, a protein bait containing spinosad as the active ingredient, has been in use as a key integrated pest management (IPM) tool against this Tephritid for the last two decades. Here, we report on resistance to spinosad [resistance ratios (RRs) and median lethal concentration (LC50 )] in Hawaii's populations of Z. cucurbitae . RESULTS: High resistance was found in populations from three farms on Oahu (RR = 102–303; LC50 = 191–567 mg L –1 ) and in a population from Maui (RR = 8.50; LC50 = 15.9 mg L –1 ). These will be problematic for control given that the most concentrated dilution ratio on the GF‐120 label is 96 mg L –1 of spinosad (1 part GF‐120 to 1.5 parts water). Background resistance in a naïve wild population from the Island of Hawaii (RR = 2.73; LC50 = 5.1 mg L –1 ) was relatively low compared with a spinosad‐susceptible laboratory colony (LC50 = 1.87 mg L –1 ). Resistance in the three Oahu and one Maui populations declined over generations in the absence of spinosad but remained elevated in some cases. Moreover, melon flies collected from one of the Oahu farms 1 year after the cessation of spinosad use revealed high persistence of resistance. CONCLUSION: Compared with a 2008 survey of spinosad resistance, our findings indicate a 34‐fold increase in resistance on one of the Oahu farms over 9 years. The evolution and persistence of high levels of resistance to spinosad in Z. cucurbitae in Hawaii highlights the need for alternative control tactics, particularly rotation of active ingredients. © 2021 The Authors. Pest Management Science published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry. Abstract : Frequent and repeated use of protein bait containing spinosad (GF‐120) in Hawaii has resulted in high levels of spinosad resistance in field populations of melon flies, which can persist for multiple generations.